Timpanometria de banda larga e emissões otoacústicas em crianças com indicadores de risco para a deficiência auditiva - Raignieri, Jéssica (2018)
Introduction: Audiological monitoring is aimed at monitoring children from six months to three years old, due to the risk of late or progressive hearing loss. Objective: To study the results of the Wideband Tympanometry in acoustic absorbance measurements and the Transient Evoked Otoacoustic Emissions and Distortion Product record in children with risk indicators for hearing loss during audiological monitoring. Method: Fifty-eight children with risk indicators for hearing loss were evaluated in the audiological monitoring process, with a mean age of 16.7 months. In order to contact the families of the children, phone calls were made, with information obtained from a database of four public maternity hospitals in São Paulo. Subjects were characterized in normal auditory status and conductive altered auditory status, in the groups with and without risk indicators for auditory deficiency, and according to the audiological results of auditory monitoring. Transient Otoacoustic Emissions and Distortion Product tests were performed, in addition to the Wideband Tympanometry. For the analysis of the absorbance in the Wideband Tympanometry, seven frequency bands were selected from 1 kHz to 8 kHz, similar to the Otoacoustic Emission Frequency bands. Results: In this study, the absorbance curves presented similar results for the right and left ears, both for children with normal hearing, and for those with conductive hearing loss, as well as for females and males. It was observed that in the frequencies between 1500 Hz and 6000 Hz, the subjects with normal hearing status, the absorbance was between 0.92 and 0.98, and the best results obtained for this age group being in this frequency range. Absorbance is higher in the group of children without risk indicators for hearing loss (RIHL) when compared to the group of children with (RIHL). The recording of Transient Otoacoustic Emissions (TOAE) and Distortion Product Otoacoustic Emissions (DPOAE) showed a strong agreement with the measured absorbance in all frequency bands in both ears. Conclusion: Absorbance values are higher in males, and for children with normal hearing status. 13 There was an agreement for the results of Evoked Otoacoustic Emissions level and absorbance measurements, and the higher the absorbance, the higher the TOAE and DPOAE levels